Heat and Flow Study of the Internally Finned Tubes with Different Fin Geometries - Evangelos Bellos; Panagiotis Lykas; Christos Tzivanidis (Applied System Innovation, 2022)
Heat and flow enhancement is a critical weapon for the design of highly efficient, compact, and cost-effective devices. The objective of this analysis is the detailed examination of the implementation of different fin shapes on the internal side of a tube aiming the heat and flow enhancement. The reference empty tube is examined, while the use of circular, rectangular, and triangular fins is also studied. Different simulations were conducted with a developed computational fluid dynamic model, and the results were expressed in heat and flow terms. The developed model was validated by comparing the results with the theoretical expressions for the Nusselt number, as well as for the friction factor. The obtained results were evaluated by calculating the heat convection coefficient, the pressure drop, the Nusselt number, the friction factor, the pump work, the mean wall temperature, and the Bejan number. According to the calculations, the use of rectangular fins is the best solution; the use of triangular fins is the second choice, while the less efficient improvement method is the use of circular internal fins. Regarding the heat transfer enhancement, the rectangular fins lead to 36% enhancement, circular fins to 25%, and triangular fins to 23% compared to the reference tube.